The Role of Contemporary Islamic Movement towards Social and Political Changes of Modernity - Suleiman, Ibrahim (American Economic & Social Review, 2017)
This paper studies the role of contemporary Islamic movements towards social and political changes of the 21st century. Contemporary Islamic movements is a modern phenomenon; it is rooted in the historically and spatially recurring cyclical phenomena of "reform" (Islah) and "renewal" (Tajdid) which provide the models and symbols that link modernity to authentic elements of Islamic teachings. The study employs secondary source as a method of data collection. Based on these past rejuvenations, contemporary Islamic scholars are interacts with modern cultural, social, political and religious circumstances. While emphasizing the Unitarian and Universalistic character of Islam, it is also coloured by local variations. Some observers see Islamic movement as part of a trend in contemporary Islam toward a more orthodox and doctrinally homogeneous type of religion based on the sacred source-texts. This trend views local expressions of Islam as deviations from orthodoxy and seeks to suppress them. Modern means of communication have accelerated this process by opening up the periphery to the penetration of the centralizing forces. In this view, Islamic movement is more radical wing of the wider movement which also includes madrasah based traditional groups and Sufi type reform movements.